Pengaruh Unsur-Unsur Kualitas Pelayanan terhadap Loyalitas Nasabah Mega First pada PT. Bank Mega, TBK Propinsi Kepulauan Bangka Belitung - Keysy Anggrayani; Ahmad Yani; Erwin Masud (LPPM STIE PERTIBA Pangkalpinang, 2019)
The purpose of this study is to determine whether tangibles, reliability, responsiveness, assurance, and empathy have an influence on customer loyalty through customer stratification as an intervening variable. This study uses 139 respondents Mega First customers at PT. Bank Mega, Bangka Belitung island province using a purposive sampling method. Sample selection criteria are Mega First customers at PT Bank Mega Tbk Bangka Belitung Islands Province. Data were analyzed using multiple linear regression models. The results showed that reliability and empathy affect customer loyalty and customer stratification affects customer loyalty. While tangibles, responsiveness, and assurance do not affect customer loyalty.